The Impact of Green Investment, Public Education, and the Use of Renewable Resources on Economic Prosperity in Indonesia - Judijanto, Loso; Adinugroho, Iwan; Tahir, Usman; Ilah, Muhammad Abdul; Sudarmanto, Eko (Westscience Press, 2024)
This study explores the impact of Green Investment, Public Education, and Renewable Resources on Economic Prosperity in Indonesia. A quantitative analysis was conducted using a sample of 160 respondents, employing a Likert scale (1-5) and data analysis through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results reveal significant positive relationships between all three independent variables (Green Investment, Public Education, Renewable Resources) and Economic Prosperity. Green Investment positively contributes to economic growth by fostering innovation and reducing environmental degradation. Public Education enhances human capital, driving productivity and economic development. Renewable Resources provide sustainable solutions for long-term energy security, job creation, and economic resilience. The study underscores the importance of integrated policies that promote sustainable investments, improve education systems, and expand the use of renewable resources to achieve long-term economic prosperity in Indonesia.